CAR, LLP, and CIR: Determinants of Islamic Commercial Banks' Financial Performance in Indonesia - Anna Julianti Amalia; Radia Purbayati; Muhammad Syaiful Nurasman (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Abstract: Financial performance instability hampers banks' intermediary function, prompting this study to analyze Capital Adequacy Ratio (CAR), Loan Loss Provision (LLP), and Cost to Income Ratio (CIR) effects on Financial Performance proxied through Return on Asset (ROA) at Indonesian Islamic Commercial Banks for the Period 2015-2023. Using quantitative descriptive methods, secondary data from 16 banks' annual reports were analyzed through panel data regression via STATA 17. The Random Effect Model was selected. Results show CAR, LLP, and CIR simultaneously significantly affect ROA. Individually, CAR positively impacts ROA, while LLP and CIR negatively affect it. These findings demonstrate that Indonesian Islamic Commercial Banks must maintain adequate capital, appropriate loss reserves, and efficient operating cost management to strengthen financial performance. Keywords: ROA, CAR, LLP, CIR